Parent involvement and children's early learning competence in literacy and mathematical understanding and approaches to learning - Berthelsen, D; Walker, S (My University, 2007)
Several studies have shown that parental involvement in a child's education has a positive effect on learning and social competence, though there are research gaps and variations. To examine this further, the authors examined parental involvement, school and teacher responsiveness, family characteristics (maternal education and income), school characteristics (whether state school or independent) and child outcome measures for literacy, numeracy, and learning approaches. The authors analysed parent and teacher surveys from the K (Kindergarten) cohort of the 'Growing Up in Australia, the Longitudinal Study of Australian Children' (LSAC), for children who are now in years 1 and 2 at primary school. This presentation outlines their findings.
Keywords: Education and Training; Education and Training -- Literacy and numeracy; Learning, education and training; Education and Training; Literacy and numeracy; Learning, education and training